Bilateral oophorectomy and the risk of hepatocellular carcinoma in women with hepatitis C: A population-based study. (April 2021) - Chen, Chao-Yu; Wang, Ting-Yao; Chen, Wei-Ming; Chen, Kai-Hua; Yang, Yao-Hsu; Chen, Pau-Chung; Chen, Vincent Chin-Hung
Highlights: People with hepatitis C infection are at high risk of developing hepatocellular carcinoma. Menopause may increase the risk of hepatocellular carcinoma. We investigated the risk of bilateral oophorectomy in women with hepatitis C. Bilateral oophorectomy did not increase the risk of hepatocellular carcinoma. Abstract: Objective: Patients with chronic hepatitis C virus (HCV) infection are at high risk of developing hepatocellular carcinoma (HCC). Previous studies suggested that menopause may increase the risk of HCC. We investigated the association between bilateral oophorectomy (BO) and the risk of HCC in women with HCV infection. Study design: We used data from the National Health Insurance Research Database of Taiwan and conducted a matched cohort study. Main outcome measures: The main outcome was HCC. We used a competing risk model to adjust for potential confounding factors. Results: From 1997–2013, we identified 2176 patients with BO and 8704 controls. A total of 107 HCC cases (4.9 %, 107/2176) were identified in the BO group compared with 465 HCC cases (5.3 %, 465/8704) in the control group. The incidence rates were 506.3 and 538.9 cases per 100, 000 person-years among the HCV-infected patients with and without BO, respectively. The competing risk model showed that BO did not increase the risk of developing HCC. Furthermore, a sub-analysis of only women under 50 years of age similarly showed that BO did not increase the risk of developing HCC after adjusting for additional covariates. The log-rank test revealed that whether or not the patients had received HRT, patients with BO did not have an increased risk of developing HCC (non-BO vs BO with HRT, p = 0.10; non-BO vs BO without HRT, p = 0.09). The use of HRT after BO did not influence the risk of developing HCC. Conclusions: This study examined a large dataset with a long follow-up period to test the relationship between BO and the risk of HCC in HCV-infected women. Our findings suggest that BO did not increase the risk of HCC, regardless of HRT usage, in these women.